PEMBERDAYAAN MASYARAKAT PERAJIN LOKAL MELALUI INOVASI PEMBUATAN BATU BELONG UNTUK ORNAMEN DAN EKSTERIOR HOTEL BERNUANSA BUDAYA BALI DI UBUD - I Made Darmada; Adhi Paramartha; Ni Nyoman Harini Puspita; I Gede Narayana (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
ABSTRACT This community service activity aims to improve the skills and creativity of local artisans through innovative production of belong stone as ornaments and for Balinese-themed hotel exteriors in Ubud. The main challenges faced include the limited technical skills of artisans in producing Balinese-based ornamental products, low product design innovation, and the suboptimal development of business opportunities and the economic value of local crafts. The activity was implemented through five stages: outreach, training, technology application, mentoring and evaluation, and program sustainability. The results showed that the belong stone training improved community skills in the design, carving, finishing, and development of Balinese ornamental motifs for hotels and villas. The application of modern technology such as electric chisels and protective coatings for natural stone also helped improve product quality and durability. Furthermore, this activity successfully increased community creativity, business opportunities, and marketing capabilities through the use of digital media. This community service program positively contributes to the development of the community's creative economy and the preservation of Balinese culture through innovative belong stone crafts with high aesthetic and economic value.